1986
DOI: 10.1007/bf01531663
|View full text |Cite
|
Sign up to set email alerts
|

Joint attention and language in autism and developmental language delay

Abstract: The relationship of gestural joint attention behaviors and the development of effective communication skills in autism and developmental language delay (DLD) was investigated. Autistic and DLD children matched for MA and MLU were compared on measures of gestural joint attention behavior, personal pronoun use, and spontaneous communicative behavior. DLD children responded correctly to joint attention interactions more often than autistic children, and their spontaneous gestural behavior was more communicative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
243
2
8

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 503 publications
(270 citation statements)
references
References 17 publications
17
243
2
8
Order By: Relevance
“…In the FR phase, Hill, 2004, for a review). It is also widely observed that individuals with ASD can show inaccurate production and reversal of pronouns (e.g., Jordan, 1989;Lee, Hobson & Chiat, 1994;Loveland & Landry, 1986;Mizuno, Liu, Williams et al, 2011). The ASD group made more source monitoring errors for self-performed actions in FR ("tell me what happened and who did what"), but not in questioning ("did Anna get the bandage or did you get the bandage?")…”
Section: Source Monitoring Of Self-and Other-performed Actionsmentioning
confidence: 99%
“…In the FR phase, Hill, 2004, for a review). It is also widely observed that individuals with ASD can show inaccurate production and reversal of pronouns (e.g., Jordan, 1989;Lee, Hobson & Chiat, 1994;Loveland & Landry, 1986;Mizuno, Liu, Williams et al, 2011). The ASD group made more source monitoring errors for self-performed actions in FR ("tell me what happened and who did what"), but not in questioning ("did Anna get the bandage or did you get the bandage?")…”
Section: Source Monitoring Of Self-and Other-performed Actionsmentioning
confidence: 99%
“…They predominantly use primitive motoric gestures (i.e., contact gesture of leading or pulling another's hand) to communicate. They lack the use of many conventional gestures, such as showing, waving, pointing, and symbolic gestures, such as nodding head and depicting actions (Loveland & Landry, 1986;McHale, Simeonsson, Marcus, & Olley, 1980;Stone & CaroMartinez, 1990;Stone et al, 1997;. In lieu of conventional means of communicating, children with ASD may develop idiosyncratic, unconventional, or inappropriate behaviors to communicate, such as self-injurious behavior, aggression, or tantrums.…”
Section: Core Social Communication Deficits In Preschool Children Witmentioning
confidence: 99%
“…Children with autism show deficiencies in joint attention behaviors (Curcio 1978;Loveland and Landry 1986;Mundy et al 1986;Wetherby and Prutting 1984). In research on autism, 'joint attention' however tends to refer to just a few of the joint attention skills such as 'gaze following,' 'pointing' behavior' and 'mutual gazing' or 'joint visual attention' (Carpenter et al 2002).…”
Section: Joint Attention Attachment and Autismmentioning
confidence: 99%